Pernicious anemia associated with cryptogenic cirrhosis: Two case reports and a literature review. Issue 39 (September 2018) - Yan, Xin; Gao, Runping; Hu, Yulin; Jin, Jinglan
Abstract: Rationale: Pernicious anemia (PA) is an autoimmune gastritis that results from the destruction of gastric parietal cells and the associated lack of an intrinsic factor to bind ingested vitamin B12. While an association between PA and various liver diseases has been rarely reported, reports of associated diseases include primary biliary cholangitis, autoimmune hepatitis, and Interferon-treated hepatitis C. We present 2 cases of PA associated with cryptogenic cirrhosis (CC), which has not been previously reported in the literature. Patient concerns: A 42-year-old man presented with fatigue, pallor, and sustained abdominal distension that had persisted for 15 days. An 87-year-old man was admitted to the hospital for an unsteady gait and loss of appetite that had persisted for 20 days. Diagnoses: Symptoms, laboratory tests, and imaging findings for both patients were indicative of PA and CC.Both had neurological and psychiatric symptoms during hospitalization that were ultimately linked to a vitamin B12 deficiency but not hepatic encephalopathy. Interventions: Both patients received intramuscular injections of vitamin B12. Outcomes: Hemoglobin levels of the 2 patients increased gradually, and their neurological symptoms were alleviated. Lessons: PA associated with a liver disease is rare, and the underlying mechanism can only now be clarified. We speculate that autoimmune dysfunction and chronic vitamin B12 deficiency caused by PA might be unique causes of liver cirrhosis. Additional investigations are needed to verify these findings.